MODЕRN TRЕNDS IN LIBRARY SЕRVICЕS (TAMADDUN NURI JURNALI, 2025)
The article examines the development trends of library and information institutions. Opinions are given on how to continuously improve the level of service in library and information institutions. It also examines aspects that have played an important role in attracting users to the library and improving its image.